A structural analysis of the work tour behavior of transit commuters. (June 2022) - Rafiq, Rezwana; McNally, Michael G.
Abstract: Our knowledge of complex travel behavior associated with transit commuting is limited. While chaining activities into tours has been a frequent behavior of travelers in general, and in some cases of work commuters, it is unclear how successful public transit has been in providing the accessibility that is needed to link multiple activities, especially on work tours. To address this knowledge gap, a structural model was developed for transit commuters, which allows for the characterization of commuters based on the complexity of work tours and an assessment of the influence of household and person-level socio-demographic characteristics, built environment variables, and activity-travel demand on tour complexity. Using data from the 2017 National Household Travel Survey, this study's results suggested that married men with no children and high vehicle ownership living in low-density areas tend to make simple work tours while single women with children who live in high-density neighborhoods were more likely to make complex work tours. Also, white men with higher incomes and higher education living in denser areas were more likely to make complex tours with work-based sub-tours. Denser residential neighborhoods, flexible work schedules, and vehicle availability on work tours were observed to increase the propensity of making complex tours. The findings of this study can assist transit agencies or planning organizations in identifying transit commuters who have complex travel needs or whose circumstances hold potential to yield greater benefits from transit usage in work tours and thus to formulate policies directed at better work and non-work travel and activity linkages.